2015
DOI: 10.1177/1535370214561953
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of WWOX in human cancer, a clinical view

Abstract: WWOX gene is located in FRA16D, the highly affected chromosomal fragile site. Its tumor suppressor activity has been proposed on a basis of numerous genomic alterations reported in chromosome 16q23.3-24.1 locus. WWOX is affected in many cancers, showing as high as 80% loss of heterozygosity in breast tumors. Unlike most tumor suppressors impairing of both alleles of WWOX is very rare. Despite cellular and animal models information on a WWOX role in cancer tissue is limited and sometimes confusing. This review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 100 publications
(165 reference statements)
0
33
0
Order By: Relevance
“…We and others have shown that chromosomal region 16q23.1 harboring FRA16D/WWOX is a hot spot for focal deletions in many human malignancies . Such allelic loses in conjunction with epigenetic and other phenomena translated to reduce WWOX mRNA and protein expression in multiple neoplasias including ovarian cancer, estrogen receptor‐negative breast cancer, esophageal and stomach cancers, among other malignancies suggesting its function as a tumor suppressor gene .…”
Section: Consequences Of Genomic Instability At Fra16dmentioning
confidence: 90%
See 3 more Smart Citations
“…We and others have shown that chromosomal region 16q23.1 harboring FRA16D/WWOX is a hot spot for focal deletions in many human malignancies . Such allelic loses in conjunction with epigenetic and other phenomena translated to reduce WWOX mRNA and protein expression in multiple neoplasias including ovarian cancer, estrogen receptor‐negative breast cancer, esophageal and stomach cancers, among other malignancies suggesting its function as a tumor suppressor gene .…”
Section: Consequences Of Genomic Instability At Fra16dmentioning
confidence: 90%
“…We and others have shown that chromosomal region 16q23.1 harboring FRA16D/WWOX is a hot spot for focal deletions in many human malignancies. 4,5,15,18,32,33 Such allelic loses in conjunction with epigenetic and other phenomena translated to reduce WWOX mRNA and protein expression in multiple neoplasias including ovarian cancer, estrogen receptor-negative breast cancer, esophageal and stomach cancers, among other malignancies suggesting its function as a tumor suppressor gene. 15,18,33 In high-resolution studies of somatic copynumber alterations performed on The Cancer Genome Atlas (TCGA) datasets, WWOX was among the genes exhibiting significant deletion in various tumor types as per GISTIC (Genomic Identification of Significant Targets in Cancer) algorithm analyses.…”
Section: Focal Deletions At Wwox Locus In Human Cancersmentioning
confidence: 99%
See 2 more Smart Citations
“…Loss of FHIT expression via promoter methylation and/or deletion have been associated with tumor progression and reduced survival in a number of cancer types 126, 127 . Homozygous and hemizygous deletions affecting the WWOX locus have been reported in several types of cancer 123, 128 and similar but less extensive data are available for some other CFS-associated genes 129 .…”
Section: Cancer and Genomic Disordersmentioning
confidence: 95%